Strategies for Improvement of Instructional Supervision in Nigeria - Makinde, Sunday Ade (Obafemi Awolowo University, 2014)
The study was designed to identify through a questionnaire the perceptions of Nigerian educators concerning alternative change strategies for improvement of instructional supervision in Nigerian public education systems. The research sample consisted of 220 Nigerian educators enrolled in colleges and universities in the southeastern United States.